Smart nanocarriers for cancer: harnessing exosomes and lipid systems in photodynamic and immunotherapy - Swain, Amrita; Jena, Soumya Ranjan; Samanta, Luna (Frontiers in Immunology, 2025)
Cancer remains the leading cause of death worldwide. Despite decades of continuous research, limitations persist in existing therapeutic approaches. Conventional strategies such as surgery, chemotherapy, and radiotherapy, though advanced, face challenges including poor bioavailability, toxic side effects, inadequate targeting of cancer cells, and limited survival benefits. The major issue lies in the inability of improved drug formulations to effectively reach cancer cells. Emerging approaches such as photodynamic therapy (PDT) and immunotherapy have shown greater promise, offering reduced side effects and higher treatment efficiency compared to traditional methods. Various natural and synthetic nanocarriers, including exosomes, liposomes, solid lipid nanoparticles (SLNs) and micelles have been explored as drug delivery vehicles in these therapies. Among them, exosomes, being natural secretory vesicles, have shown unique potential as independent delivery systems. However, challenges and limitations remain in their application for precise cancer targeting. A combinational strategy, integrating exosomes with other lipid-based drug delivery systems (LBDDS), while preserving their intrinsic properties and engineering their surface to carry photosensitizers (PS) or immune modulators, could overcome these barriers. Such well-designed natural cargos may enhance therapeutic efficacy, modulate the tumor microenvironment, and address current shortcomings in cancer therapy. This review highlights the individual applications of PDT and immunotherapy using exosomes and LBDDS, and explores their potential synergistic use for more effective and targeted cancer treatment.